Anti-fibrotic effects of Cuscuta chinensis with in vitro hepatic stellate cells and a thioacetamide-induced experimental rat model - Jin Seoub Kim; Sushruta Koppula; Mun Jeong Yum; Gwang Mo Shin; Yun Jin Chae; Seok Min Hong; Jae Dong Lee; MinDong Song (Taylor & Francis Group, 2017)
Context: Cuscuta chinensis Lam. (Convolvulaceae) has been used as a traditional herbal remedy for treating liver and kidney disorders. Objective: Anti-fibrotic effects of C. chinensis extract (CCE) in cellular and experimental animal models were investigated. Materials and methods: HSC-T6 cell viability, cell cycle and apoptosis were analysed using MTT assay, flow cytometry and Annexin V-FITC/PI staining techniques. Thioacetamide (TAA)-induced fibrosis model was established using Sprague Dawley rats (n = 10). Control, TAA, CCE 10 (TAA with CCE 10 mg/kg), CCE 100 (TAA with CCE 100 mg/kg) and silymarin (TAA with silymarin 50 mg/kg). Fibrosis was induced by TAA (200 mg/kg, i.p.) twice per week for 13 weeks. CCE and silymarin were administered orally two times per week from the 7th to 13th week. Fibrotic related gene expression (α-SMA, Col1α1 and TGF-β1) was measured by RT-PCR. Serum biomarkers, glutathione (GSH) and hydroxyproline were estimated by spectrophotometer using commercial kits. Results: CCE (0.05 and 0.1 mg/mL) and silymarin (0.05 mg/mL) treatment significantly (p < 0.01 and p < 0.001) induced apoptosis (11.56%, 17.52% for CCE; 16.50% for silymarin, respectively) in activated HSC-T6 cells, compared with control group (7.26%). Further, rat primary HSCs showed changes in morphology with CCE 0.1 mg/mL treatment. In in vivo studies, CCE (10 and 100 mg/kg) treatment ameliorated the TAA-induced altered levels of serum biomarkers, fibrotic related gene expression, GSH, hydroxyproline significantly (p < 0.05-0.001) and rescued the histopathological changes. Conclusions: CCE can be developed as a potential agent in the treatment of hepatofibrosis.